Current Status and Threats to Himalayan Birch and Its Socio-economic Impact on Local Community in Baltistan (Pakistan) (Journal of Asian Development Studies, 2025)
This study intends to evaluate the birch forest's current status and identify the main threats to the birch forest in District Skardu, Baltistan, Pakistan. This study aimed to investigate the connection between problems and anthropogenic activities, and threats, which had negatively affected the ratio of Birch trees in District Skardu, Gilgit Baltistan. The research has highlighted the importance of forest-based industry as its socioeconomic impact on the local community. A questionnaire was used to determine the socioeconomic importance and hazards facing the birch forest, highlighting issues like fuelwood gathered, deforestation, climate change, and catastrophic events. Additionally, Tehsil Roundu, District Skardu, used random fixed plot sampling to evaluate the forest. The studies stated 75% of people in rural areas including the urban area used Birch forest for, packing purposes, furniture making, and other anthropogenic activities due to mentioned factors it declared as threatened species. In the previous studies and records of 10 to 15 years, comparatively the Birch forest has declined 5 to 6%, which is a serious threat and environmental challenge. About 88% of people responded that deforestation is the primary driver in the reduction of Birch forest status, the studies also revealed that 75% of local communities used it for fuel wood and furniture making, 69% believed that it could be best used for multiple disease treatment.